1999
DOI: 10.1161/01.atv.19.8.1969
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Gene Polymorphism and Carotid Wall Thickening in a Community Population

Abstract: Abstract-The insertion/deletion (I/D) polymorphism of the angiotensin-converting enzyme (ACE) gene has been associated with an increased risk of coronary heart disease, but whether it is a risk factor for underlying atherosclerosis remains unclear. Therefore, we examined to see whether the ACE gene deletion polymorphism was associated with carotid wall thickening and atherosclerotic plaque formation in a large randomly selected community population. A total of 1111 subjects, aged 27 to 77 years, with an equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 34 publications
3
34
2
1
Order By: Relevance
“…Although some studies suggested associations between the ACE D allele and increased carotid intima-medial thickness, 19 carotid plaque, 20 carotid stenosis, 21 and ischemic stroke, 22 the findings of PROGRESS confirm other negative association analyses. [23][24][25][26] Patients with cerebrovascular disease, though at very high risk of stroke, also have substantially elevated risks of myocardial infarction and other cardiac events. 27 In the PROGRESS study, 150 incident cases of nonfatal myocardial infarction and a total of 255 major coronary events were observed in the genotyped subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggested associations between the ACE D allele and increased carotid intima-medial thickness, 19 carotid plaque, 20 carotid stenosis, 21 and ischemic stroke, 22 the findings of PROGRESS confirm other negative association analyses. [23][24][25][26] Patients with cerebrovascular disease, though at very high risk of stroke, also have substantially elevated risks of myocardial infarction and other cardiac events. 27 In the PROGRESS study, 150 incident cases of nonfatal myocardial infarction and a total of 255 major coronary events were observed in the genotyped subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes-related data including duration were Insertion/deletion (I/D) polymorphisms of the ACE gene were detected by validated PCR supplemented by restriction typing of PCR products (27). The A1166C polymorphism in ATR1 was identified using mutagenically separated PCR, with an A-allele-specific forward primer, a C-allele-specific forward primer and a reverse primer, with separation of PCR products on 3% agarose gel (27). APOE genotype was determined via PCR amplification and restriction enzyme digestion (28).…”
Section: Clinical Assessment and Laboratory Testsmentioning
confidence: 99%
“…Some studies have yielded suggestive results for the T/T genotype of the b-fibrinogen gene, 38 factor V Leiden, 39 the D/D genotype of the angiotensin-converting enzyme insertion/deletion polymorphism, 40 and the paraxonase gene, 38 whereas others have not found a relationship. 31,[41][42][43][44] In our analysis, heritability was only modestly attenuated by adjustment for known cardiac risk factors, suggesting that genes implicated in the variability of these phenotypes may not be major contributors to carotid IMT.…”
Section: Fox Et Al Heritability Of Carotid Intima-media Thicknessmentioning
confidence: 61%